Stres Akademik siswa dimasa pandemi covid-19 dan Penanganannya (Studi kasus pada seorang siswa di SMPN 4 Palopo menggunakan pendekatan solution focus brief counseling) - Rahmaniar Andi syahrir (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This research discusses Academic Stress during the Covid-19 pandemic while studying from home experienced by a student at SMP Negeri 4 Palopo. The approach in this research is a qualitative approach with the type of case study research.  Data analysis used descriptive analysis with triangulation technique. The results obtained are: (1) The description of the stress felt during learning from home includes anxiety, boredom, sadness, feeling neglected, irritable, dizzy, not feeling satisfied to lazy learning behavior during the pandemic. (2) Factors that influence academic stress while studying from home are external and internal factors, pessimism in learning, not recognizing their potential, not yet adapting, and being responsible for learning. (3) Providing short counseling focused on solutions that can make students feel optimistic in learning, recognize potential, goals, and the right way to manage time with a schedule made by themselves in order to deal with academic stress problem in a student at SMP Negeri 4 Palopo.